2012
DOI: 10.1557/opl.2012.1496
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth Activated Glass and Glass-Ceramic for Neutron Detection

Abstract: Neutron detection scintillators based on rare-earth activated transparent glass and glass-ceramics are reported. Ce 3+ doped gadolinium halides in 6 LiF modified aluminosilicate glass matrices were synthesized by a melt-quench method followed by annealing. Their optical properties and alpha, neutron scintillation performance were investigated and compared to conventional 6 Li-based scintillating glass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“… The mean decay time values for No.2, 3 and 4 glasses are evaluated to be about 14.69, 23.34, and 24.47 ns, respectively. It is found that the decay times of Ce 3+ ions in the investigated borogermanate glasses is very close to those in the famous fluorohafnate‐based scintillating glasses , which are much shorter than Ce 3+ ions in borosilicate, phosphate , and other oxyfluoride aluminosilicate glasses …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… The mean decay time values for No.2, 3 and 4 glasses are evaluated to be about 14.69, 23.34, and 24.47 ns, respectively. It is found that the decay times of Ce 3+ ions in the investigated borogermanate glasses is very close to those in the famous fluorohafnate‐based scintillating glasses , which are much shorter than Ce 3+ ions in borosilicate, phosphate , and other oxyfluoride aluminosilicate glasses …”
Section: Resultsmentioning
confidence: 99%
“…Fast Ce 3+ ‐activated scintillating glass is one of the most promising candidates for scintillators in medical imaging, homeland security, high energy, and nuclear physics owing to the advantages of its low cost, large‐volume production, and easy shaping of elements . From the viewpoint of application in high‐energy physics engineering, scintillating materials exceeding 5.0 g/cm 3 are particularly interesting because dense scintillating glass enlarges the X‐ray absorption cross section, which improves the image signal‐to‐noise ratio .…”
Section: Introductionmentioning
confidence: 99%